Role performance of public secondary school principals in the in-service education of teachers in the Division of City Schools, Manila - Manduan Doungnet 1941- (1973)
Twenty-five principals and 41 assistant principals reported that they always (a) work cooperatively with the staff, (b) stimulate the teachers to share there opinions, and (c) provide an atmosphere conducive to work. They had done more in the area of evaluation than in the implementation and initiation areas, providing additional help in evaluation and providing ways and means of evaluating inservice education programs. Very few of the principals indicated problems met in relation to inservice education. The few problems included providing facilities and selecting the place for in-service training.
Vita.
Thesis (M.A. Educational Administration)--University of the Philippines, Diliman.
Keywords: High school principals -- Philippines -- Manila; High school teachers -- In-service training -- Philippines -- Manila